PENGEMBANGAN ZONA INTEGRASI ANTARMODA STASIUN LRT DI JEMBATAN AMPERA (FSTPT Indonesia, 2023)
The Unavailability of Palembang City Transportation, which does not cover all the main destinations of Palembang City, causes passengers who want to continue their journey by public transportation to not be served properly due to the limitations of onward transportation services at the station. Intermode integration is one way to increase occupancy on the South Sumatera province. With the integration, passengers who desire to reach their destinations can switch modes safely and comfortably. The purpose of this study is to identify the existing conditions of advanced transportation at Ampera station, analyze the characteristics of passenger demand for onward transportation and the appropriate scheduling of advanced transportation in serving the needs of passengers. This study aims to determine the level of passenger demand for advanced modes after using the South Sumatera LRT. This study uses Peak Hours Analysis, Passengger Needs Analysis, Load Factor Analysis, and scheduling analysis. Based on the results of the analysis, it can be concluded that results of the analysis that the willingness of passengers to change modes and scheduled is 90%. ABSTRAK Ketidaktersediaan Angkutan Kota Palembang yang tidak menjangkau seluruh tujuan utama Kota Palembang menyebabkan penumpang yang ingin melanjutkan perjalanan dengan angkutan umum tidak terlayani dengan baik dikarenakan keterbatasan layanan angkutan lanjutan di stasiun. Integrasi antarmoda merupakan salah satu cara agar okupansi pada LRT Sumatera Selatan meningkat. Dengan adanya integrasi, penumpang yang ingin mencapai tujuan dapat beripindah moda dengan aman dan nyaman.Tujuan dari penelitian ini adalah mengidentifikasi kondisi eksisting angkutan lanjutan yang ada di stasiun ampera, menganalisis karakteristik permintaan penumpang terhadap angkutan lanjutan dan penjadwalan angkutan lanjutan yang tepat dalam melayani kebutuhan penumpang. Penelitian ini bertujuan untuk mengetahui tingkat kebutuhan penumpang terhadap moda lanjutan setelah menggunakan LRT Sumatera Selatan. Penelitian ini menggunakan Analisis Peak Hours, Analisis Kebutuhan Penumpang, Analisis Faktor muat, dan analisis penjadwalan. Dan Berdasarkan hasil analisis dapat disimpulkan kemauan penumpang untuk berpindah moda dan terjadwal sebanyak 80%.